Environmental impact of developing large buildings close to residential environments - Zhunussova, Meruyert; Jaeger, Martin; Adair, Desmond (Institute of Electrical and Electronics Engineers Inc., 2016)
High-resolution computational fluid dynamics (CFD) simulations have been performed to access the dispersion of air pollutants (CO2) emanating from traffic in a busy street and in the vicinity of a complex configuration of buildings located in Salmiya, Kuwait City.
Keywords: air quality; built environment; Computational Fluid Dynamics; street canyon; Research Subject Categories::TECHNOLOGY::Engineering physics